2013
DOI: 10.1371/journal.pone.0079314
|View full text |Cite|
|
Sign up to set email alerts
|

Soothing the Threatened Brain: Leveraging Contact Comfort with Emotionally Focused Therapy

Abstract: Social relationships are tightly linked to health and well-being. Recent work suggests that social relationships can even serve vital emotion regulation functions by minimizing threat-related neural activity. But relationship distress remains a significant public health problem in North America and elsewhere. A promising approach to helping couples both resolve relationship distress and nurture effective interpersonal functioning is Emotionally Focused Therapy for couples (EFT), a manualized, empirically suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Interventions aiming at improving attachment security by removing the barriers in front of partners’ responsive behaviors toward each other have already been shown to be effective in alleviating marital distress over time (Johnson, et al, 2013) and such interventions targeting marital strains and strengths may lead to beneficial psychological and physiological changes conducive to a healthier and longer life.…”
Section: Moving Forward With Greater Interdisciplinary Integrationmentioning
confidence: 99%
“…Interventions aiming at improving attachment security by removing the barriers in front of partners’ responsive behaviors toward each other have already been shown to be effective in alleviating marital distress over time (Johnson, et al, 2013) and such interventions targeting marital strains and strengths may lead to beneficial psychological and physiological changes conducive to a healthier and longer life.…”
Section: Moving Forward With Greater Interdisciplinary Integrationmentioning
confidence: 99%
“…For example, Johnson et al (2013) compared the ability of spousal hand-holding to buffer neural responses to threat before and after couples underwent Emotion-Focused Therapy (EFT). They found that EFT increased the ability of hand-holding to attenuate threat responses; similar examination of both parent and child neural activity in response to attachment-related interventions would be informative.…”
Section: Attachment and Psychopathology: Gaps In The Research And Futmentioning
confidence: 99%
“…Finally, predictions regarding SOS support enabling an individual to thrive are also supported by research showing that responsive social support in times of adversity is linked to long-term relationship outcomes in couples including increased satisfaction, intimacy, and trust [8,27], and by research showing that interventions designed to increase availability and responsiveness between couple members increases relationship quality and alters the brain’s representation of threat cues in the presence of a romantic partner [28]. …”
Section: Empirical Evidencementioning
confidence: 99%